MOOD AND TRANSITIVITY SYSTEM IN THE DIALOGUE OF NOVEL ENTITLE „THE FAULT IN OUR STARS‟: SYSTEMIC FUNCTIONAL LINGUISTIC STUDIES - John Berdy Gustafito; I Gusti Nyoman Putra Kamayana (LITERA : Jurnal Bahasa Dan Sastra, 2016)
ABSTRACTThis research is focused on the analysis of the interpersonal meaning and transitivity system inthe novel entitle „The Fault in Our Stars‟. This research aims to describe the interpersonalmeaning (mood) whether it is declarative (statement), interrogative (question), imperative(command), or subjunctive mood (wish/request) and the transitivity system in the dialoguebetween characters of the novel in order to describe the realization of linguistic experience ofthe character in novel whether which entangle processes, participants, and circumstance. Thetheory used in this research is the theory of Systemic Functional Linguistic (SFL) proposed byHalliday focusing on text, the text in this case is novel. The data were collected by note takingand randomly taken from the dialogue in the novel, afterward, analyzed to find out the moodusage and transitivity system used in the dialogue. This study uses a qualitative descriptiveapproach. The result shows that from the data sample there are five processes of transitivitysystem found in this study namely; mental, material, existential, verbal, and relational.Keyword: Novel, SFL, Interpersonal, Transitivity.ABSTRAKPenelitian ini difokuskan pada analisis makna interpersonal dan sistem transitivitas dalam novelberjudul 'The Fault in Our Stars'. Penelitian ini bertujuan untuk mendeskripsikan maknainterpersonal (mood) apakah itu deklaratif (pernyataan), interogatif (pertanyaan), perintah(perintah), atau suasana hati subjungtif (wish / request) dan sistem transitivitas dalam dialogantara karakter novel Untuk menggambarkan realisasi pengalaman linguistik karakter dalamnovel apakah yang melibatkan proses, peserta, dan keadaan. Teori yang digunakan dalampenelitian ini adalah teori Systemic Functional Linguistic (SFL) yang diajukan oleh Hallidayyang berfokus pada teks, teks dalam hal ini adalah novel. Data dikumpulkan dengan mencatatdan diambil secara acak dari dialog dalam novel tersebut, kemudian dianalisis untukmengetahui penggunaan mood dan sistem transitivitas yang digunakan dalam dialog. Penelitianini menggunakan pendekatan deskriptif kualitatif. Hasil penelitian menunjukkan bahwa daridata sampel terdapat lima proses sistem transitivitas yang ditemukan pada penelitian ini yaitu;Mental, material, eksistensial, verbal, dan relasional.Kata kunci: novel, sfl, interpersonal, transitivitas